Examining Walking-Waiting Sexual Assaults from Previously Untested Sexual Assault Kits: The Intersection of Stranger and Outdoor Sexual Assaults - Lovell, Rachel E. (Victims & offenders, 2024)
Within a routine activity framework, we explore walking-waiting sexual assaults – committed by strangers when victims were outdoors and did not consensually leave the scene. With data from untested sexual assault kits spanning decades in one urban jurisdiction, we found these were common (a fourth of the sample) with a distinct offending pattern. African American women were identified as the most frequent “targets” due to the use of certain public spaces that appear to lack “capable guardianship.” “Motivated offenders” were often serial sexual offenders but not exclusively tied to walking-waiting sexual assaults. Findings improve our understanding of the intersection of stranger and outdoor sexual assaults. Implications and future directions discussed.